USING OF THE MORPHOSTRUCTURAL ANALYSIS AND LASER ATOMIC-EMISSION SPECTROMETRY FOR DIAGNOSTICATION OF PROSTATE CANCER - G. T. Maslova (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The morphology of dried blood plasma from patients with oncopathology has been studied. The structural features characteristic for the dried drops of blood plasma from the patients with diagnosed carcinoma of the prostate have been revealed. Semiquantitative estimates of the spatial distribution of calcium over the surface of the dried drops of biological fluids have been obtained using laser atomic-emission spectrometry. Owing to the use of this method, one can have quantitative estimates of changes in the protein centers. The possibility for making more accurate diagnoses by means of attribution of the tumor to the types Т2 and Т3 or Т4 is demonstrated. The obtained experimental results may form the basis for the development of early cancer diagnostication techniques.